Heart Disease, Longevity, and Cholesteryl Ester Transfer Protein - Vijayakumaran, Vithooshan; Dattani, Neil D. (My University, 2010)
Genetics is a rapidly expanding field of biology. It is only within the last 25 years that whole genomes have been sequenced. At first the genomes that were sequenced were small such as that of H. Influenza and C. Elegans. More recently, however, larger more expensive projects have tackled more complex genomes; one of these was the human genome project. Since its completion in 2003, continued analysis and breakthroughs in sequencing technology have allowed for genetic counselling and genetic screens for diseases that have been linked to genetic disorders. Genetic screens allow people to determine whether they or their offspring are likely to develop certain diseases but besides providing only bad news, genetic screening can also determine whether someone possesses a beneficial trait. For example, individuals with mutations in genes such as the one encoding the cholesteryl ester transfer protein have been found to have gained advantages such as a reduced risk of arterial and cognitive disease and an increased lifespan. This paper outlines the physiology of cholesteryl ester transfer protein, and elucidates its potential role in human health.
Keywords: CETP; cholesteryl ester transfer protein; heart disease; cardiovascular disease; Cardiovascular Diseases; Circulatory and Respiratory Physiology; Genetic Processes; Molecular Biology; Cardiovascular Diseases